2011
DOI: 10.1016/j.cognition.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and representational integration: Evidence from speech errors

Abstract: We examine the mechanisms that support interaction between lexical, phonological and phonetic processes during language production. Studies of the phonetics of speech errors have provided evidence that partially activated lexical and phonological representations influence phonetic processing. We examine how these interactive effects are modulated by lexical frequency. Previous research has demonstrated that during lexical access, the processing of high frequency words is facilitated; in contrast, during phonet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 56 publications
(109 reference statements)
2
44
0
Order By: Relevance
“…The concept of phonetic accommodation is at odds with several recent empirical studies that report that in error-inducing environments, VOT values reflect the competition of multiple items during planning (Goldrick, Baker, Murphy, & Baese-Berk, 2011;Goldrick & Blumstein, 2006;McMillan & Corley, 2010;McMillan, Corley, & Lickley, 2009). For example, for audibly identified voicing errors in keff geff alternations, subjects' VOT values differed significantly from both correctly produced voiceless and correctly produced voiced productions, even though the differences were below 8 ms (Goldrick & Blumstein, 2006).…”
mentioning
confidence: 49%
“…The concept of phonetic accommodation is at odds with several recent empirical studies that report that in error-inducing environments, VOT values reflect the competition of multiple items during planning (Goldrick, Baker, Murphy, & Baese-Berk, 2011;Goldrick & Blumstein, 2006;McMillan & Corley, 2010;McMillan, Corley, & Lickley, 2009). For example, for audibly identified voicing errors in keff geff alternations, subjects' VOT values differed significantly from both correctly produced voiceless and correctly produced voiced productions, even though the differences were below 8 ms (Goldrick & Blumstein, 2006).…”
mentioning
confidence: 49%
“…On the other side of the coin, the fact that /r/-sandhi in the UK dataset was not influenced by lexical frequency is incompatible with classical Exemplar Theory, which predicts that sound patterns should always be more advanced (that is, manifest at higher rates) in higher frequency words. The answer to the first research question thus appears to be that knowledge supporting sound patterns can be both abstract and word-specific, supporting hybrid theories of phonological knowledge (e.g., Buchwald and Miozzo, 2011;Goldrick, Ross Baker, Murphy, & Baese-Berk, 2011;Levelt et al, 1999;Pierrehumbert, 2006). Having shown that lexically specific information can influence /r/-sandhi, we can ask whether speakers store all or just a subset of the phonetic detail available to them.…”
Section: Discussionmentioning
confidence: 96%
“…For example, it has been shown that relatively few exposures to pronunciations of low-frequency words can modulate the way these words are pronounced (e.g., Goldinger, 1998). Goldrick et al (2011) have shown that low-frequency words -which have stronger, more narrowly defined phonetic representations -leave stronger traces of target phonemes in the errors than high-frequency words. These influences will be possible only if the phonetics of the low-frequency words is stored and able to modulate subsequent production or the effect of errors.…”
Section: Implications For Model Of Speech Productionmentioning
confidence: 98%